Special Ops: Lioness - Freeman, Morgan 1937-; Saldana, Zoë 1978-; Oliveira, Laysla de 1992-; Kidman, Nicole 1967-; Sheridan, Taylor 1970-; Kelly, Michael 1969- (Universal Pictures Germany GmbH, 2024)
"Follows the life of Joe while she attempts to balance her personal and professional life as the tip of the CIA's spear in the war on terror. The Lioness Program, overseen by Kaitlyn Meade and Donald Westfield, enlists an aggressive Marine Raider named Cruz to operate undercover alongside Joe among the power brokers of State terrorism in the CIA's efforts to thwart the next 9/11"--
Staffel 1-
TV-Serie; Action; Thriller; Drama, 2023-
Keywords: Television series; Action films; Thrillers; Melodramas; Actionfilm; Melodrama; Fernsehserie; Thriller; United States / Central Intelligence Agency / Drama; Special operations (Military science) / Drama; Terrorism / Drama; Action and adventure television programs; Thrillers (Television programs); Fiction television programs; Video recordings for the hearing impaired; Émissions d'aventures télévisées; Thrillers (Émissions télévisées); Séries télévisées; Fictions télévisées; Vidéos pour personnes handicapées auditives; DVD-Video